Model Implementation Trap of Policy New Student Acceptance Zoning System in Makassar City - Nuryanti Mustari; Rudi Hardi; Amir Muhiddin (Journal of Government and Civil Society, 2021)
Implementing the zoning system in the 2019/2020 school year imposed by the Makassar city government through the Education Office caused various problems. This study's specific purpose is (1) To examine the characteristics of the New Student Acceptance problem of the zoning system, (2) explore the supporting capacity of the regulations, 3. non-regulatory environmental factors that affect the implementation of the PPDB zoning system. 4. Implementation trap of policy. The Research Method used is a qualitative method, and the appropriate type of research is a case study.  The results showed that the New Student Acceptance problem zoning system characteristics, among others: Infrastructure readiness problems for online registration, Lack of socialization of PPDB system to prospective students and parents, thus confusing. The implementation trap of policy, the policy objective is too vague or broad to be converted into action, the target specification is not clearly defined due to weak guidelines on how goals can be achieved, or undefined standards or actions to be taken, either in implementing, or the target community. Finally, problems also arise when the chain of responsibility for implementing a policy is unclear.Penerapan sistem zonasi pada tahun ajaran 2019/2020 yang diberlakukan pemerintah kota Makassar melalui Dinas Pendidikan menimbulkan berbagai permasalahan. Tujuan khusus penelitian ini adalah (1) Untuk meneliti karakteristik masalah Penerimaan Siswa Baru dari system zonasi, (2) mengeksplorasi daya dukung peraturan, 3. Factor lingkungan non-regulasi yang mempengaruhi penerapan system zonasi PPDB. 4. Perangkap implementasi kebijakan. Metode Penelitian yang digunakan adalah metode kualitatif, dan jenis penelitian yang sesuai adalah studi kasus.  Hasil penelitian menunjukkan bahwa karakteristik system zonasi masalah Penerimaan Siswa Baru antara lain: Masalah kesiapan infrastruktur untuk pendaftaran online, Kurangnya sosialisasi sistem PPDB kepada calon siswa dan orang tua, sehingga membingungkan. Jebakan implementasi kebijakan  , tujuan kebijakan terlalu kabur atau luas untuk dikonversi menjadi tindakan, spesifikasi target tidak didefinisikan dengan jelas karena pedoman yang lemah tentang bagaimana tujuan dapat dicapai, atau standar atau tindakan yang tidak terdefinisi untuk diambil, baik dalam menerapkan, atau komunitas target. Akhirnya, masalah juga muncul ketika rantai tanggung jawab untuk menerapkan kebijakan tidak jelas.